2019
DOI: 10.9734/cjast/2019/v38i330362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Background Ionizing Radiation Level of Selected Oil Spill Communities of Delta State, Nigeria

Abstract: Study of the terrestrial Background Ionizing Radiation levels of selected Oil Spill Communities of Delta State, Nigeria have been carried out using Digilert 200 and Radalert 100 nuclear radiation monitor and a geographical positioning system (Garmin GPSMAP 76S). The exposure rates of the five communities ranges from 0.016 to 0.030  at Jones Creek, 0.014 to 0.034  at Opuwade Community, 0.015 to 0.037   at Okpare community, 0.007 to 0.029  at OtuJeremi community and 0.011to 0.040  at Otor-Edo community. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
2
3
4
Order By: Relevance
“…These values are higher than the world permissible value of 0.29 x 10 -3 but are in agreement with results of previous studies in similar environment for example as reported by Audu et al, 2019. Effective Dose to human Organ or Tissue: Bone marrow, Lungs, Ovaries, Testes, Liver, Kidney and Whole body were considered and their respective calculated values are 0.52, 0.48, 0.43, 0.61, 0.34, 0.46 and 0.51 mSvy -1 . These values are far below the standard value of 1.0 mSvy -1 .…”
Section: Background Ionizing Radiation (Bir) Exposure Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…These values are higher than the world permissible value of 0.29 x 10 -3 but are in agreement with results of previous studies in similar environment for example as reported by Audu et al, 2019. Effective Dose to human Organ or Tissue: Bone marrow, Lungs, Ovaries, Testes, Liver, Kidney and Whole body were considered and their respective calculated values are 0.52, 0.48, 0.43, 0.61, 0.34, 0.46 and 0.51 mSvy -1 . These values are far below the standard value of 1.0 mSvy -1 .…”
Section: Background Ionizing Radiation (Bir) Exposure Levelssupporting
confidence: 93%
“…This minimum range exceeded the world recommended value of 13 µRh -1 , and the same maximum value was recorded at MBR, OTW and EGB. These values are in agreement with values recorded at selected oil spill communities in Delta State (Audu et al, 2019). Mean BIR ranged from 19.83±2.3 (FLS) to 27.67±2.42 µRh -1 (OTW).…”
Section: Background Ionizing Radiation (Bir) Exposure Levelssupporting
confidence: 89%
“…The absorbed dose rates arising from the BIR levels of the masts and the annual effective radiation doses at these rates do not constitute any immediate radiological health effect on the mast workers and the general public. The values for the cancer risks obtained in this work are far higher than the average value of 0.29×10-3 as recommended by UNSCEAR [34,36]. The implication of this is that workers who visit the base stations on daily basis and members of the public who either live or work few meters away from the stations and end up spending long hours within the stations are likely to develop cancer at ages of 65 to 70 years or above of their lifetime.…”
Section: Resultscontrasting
confidence: 66%
“…The mean absorbed dose of BIR exposure is 147.3887 nGyh -1 while the mean annual effective dose equivalent of the mill is 0.1804 mSvy -1 . The absorbed doses in the entire rice mills are far higher than those reported in literature [8][9][10][11][12][13][14][15]19] and also above the recommended safe limit of 84.0 nGyh -1 [34,35]. Radiation levels increase as one gets closer to the source, so the high amount of absorbed radiation recorded in this work may have come from the rice grain and husks which the workers are always in contact with.…”
Section: Resultsmentioning
confidence: 99%
“…Ife-Adediran and Uwadiae [18] evaluated background ionizing radiation from different buildings in Lagos and Ibadan, Nigeria and found the indoor dose rates to be within the world average values while the AED for most of the buildings were above the world average for indoor gamma exposure from building materials. A baseline study of terrestrial outdoor gamma dose rate levels in Nigeria revealed that the mean annual effective dose equivalent in Nigeria is 0.27 mSvy -1 [19].…”
Section: Introduction mentioning
confidence: 99%